Translation of innovative chemistry into screening libraries: an exemplar partnership from the European Lead Factory. Issue 9 (September 2018) - Morgentin, Remy; Dow, Mark; Aimon, Anthony; Karageorgis, George; Kalliokoski, Tuomo; Roche, Didier; Marsden, Stephen; Nelson, Adam
Highlights: Partnership translated academic chemistry into screening libraries. Many molecular scaffolds were sp 3 -rich and natural-product-like. A blueprint for exploiting innovative chemistry in discovery. Abstract : The identification of high-quality starting points for drug discovery is an enduring challenge in medicinal chemistry. Yet, the chemical space explored in discovery programmes tends be limited by the narrow toolkit of robust methods that are exploited in discovery workflows. The European Lead Factory (ELF) was established in 2013 to boost early-stage drug discovery within Europe. In this Feature, we describe an exemplar partnership that has led to the addition of 21 119 distinctive screening compounds to the ELF Joint European Compound Library. The partnership could serve as a blueprint for the translation of innovative academic chemistry into discovery programmes.